Readiness Assessment of Pasuruan Industrial Estate Rembang (PIER) Towards Sustainable Industrial Estate - Hotnida Nainggolan; Ni Wayan Surya Wardhani; Amin Setyo Leksono; Imam Santoso (Jurnal Sumberdaya Alam dan Lingkungan, 2021)
ABSTRACTGlobal awareness towards sustainability are putting pressure on industries worldwide to implement procedures to manage the elements of sustainability for an industrial development. This study aims to assess the readiness of Pasuruan Industrial Estate Rembang (PIER) towards sustainable industrial estate. This research was conducted using qualitative methods with the type of research in the form of case studies. Six parameters are assessed based on the concept formulated by Ernest Lowe (2001) that include natural system integration with environmental capacity-bearing capability, sustainable energy and water use, integration of output and waste material flows, efficient industrial estate management, environmentally friendly infrastructure design and integration between industrial estates and social communities, contributing to local economic development. Using a Likert scale of 1 to 3 to assess the level of application of EIP principles in the PIER industrial estate, the results obtained are that two EIP principles have not been applied at all and four principles have not been fully implemented.Keywords: assessment, scales, sustainability